Anti‐cancer potentials of Gynura procumbens leaves extract against two canine mammary cancer cell lines. Issue 1 (9th December 2021) - Jermnak, Usuma; Supsavhad, Wachiraphan; Kunakornsawat, Sunee; Jaroensong, Tassanee; Watcharasit, Piyajit; Visitnonthachai, Daranee; Pairor, Selapoom; Phaochoosak, Napasorn
Abstract: Background: The anti‐cancer effects of Gynura procumbens leaves extract (GPE) have been reported in various human cancers. However, the anti‐cancer effects and molecular mechanisms of this extract on canine mammary cancer (CMC) have not yet been elucidated. Objectives: The main goal of this study was to investigate the anti‐cancer properties of GPE against two CMC cell lines (CHMp‐13a and CHMp‐5b). Methods: The GP leaves were extracted with 80% ethanol. Anti‐cancer potentials of GPE on CHMp‐13a and CHMp‐5b cancer cell lines using dimethyl‐2‐thiazolyl‐2, 5‐diphenyl‐2H‐tetrazolium bromide (MTT), wound healing, transwell migration, and caspase 3/7 activity assays were evaluated. The mRNA expression levels of two oncogenes: epidermal growth factor receptor ( EGFR ) and twist family bHLH transcription factor 1 ( TWIST ) and one tumour suppressor gene: phosphatase and tensin homolog ( PTEN ) in these cell lines were determined by quantitative real‐time PCR (qRT‐PCR). In addition, The EGFR and PTEN protein levels as well as protein kinase B (AKT) and extracellular signal‐regulated kinase 1/2 (ERK1/2) phosphorylation levels expression were also evaluated by western blot analysis. Results: The results showed that GPE caused a significant concentration‐ and time‐dependent reduction in cell proliferation of both CHMp‐13a and CHMp‐5b cells, detected by MTT assays. This extract also significantly suppressed cancer cell migration in both cell lines, tested by wound healing and transwell migration assays. Additionally, the increase in caspase 3/7 activity observed in both CMC cell treated with GPE suggests that GPE induced caspase 3/7 dependent apoptosis. Moreover, GPE significantly decreased EGFR mRNA and protein expression levels compared to control in both cell lines in a dose‐dependent manner. Conclusion: These findings emphasized that GPE has an in vitro anti‐cancer activity against CMC by inhibiting EGFR signalling pathway. Thus, GPE may serve as an alternative therapy in CMC with high EGFR expression. Abstract : The anti‐cancer properties of Gynura procumbens leaves extract were investigated in two canine mammary cancer cell lines. The results indicate that this herbal extract inhibits the cell proliferation and migration, and induces apoptosis of both cancer cell lines via the inhibition of EGFR signalling pathway. Therefore, Gynura procumbens leaves extract may serve as an alternative therapy in mammary cancer in dogs with high EGFR expression.